2022
DOI: 10.15252/embj.2021110023
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell transcriptomics uncovers an instructive T‐cell receptor role in adult γδ T‐cell lineage commitment

Abstract: After entering the adult thymus, bipotent T-cell progenitors give rise to ab or cd T cells. To determine whether the cd T-cell receptor (TCR) has an instructive role in cd T-cell lineage commitment or only "confirms" a pre-established cd Τ-cell lineage state, we exploited mice lacking expression of LAT, an adaptor required for cd TCR signaling. Although these mice showed a T-cell development block at the CD4 À CD8 À double-negative third (DN3) stage, 0.3% of their DN3 cells expressed intermediate levels of cd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
(58 reference statements)
1
9
0
Order By: Relevance
“…High Trdc, Id3, Sox13 and Rorc identified mature γδ thymocytes (Fig 2D). This analysis revealed that multiple distinct populations correspond to each of the canonical DN stages and consistent with recent T cell development studies (Spidale et al, 2018;Sagar et al, 2020;Scaramuzzino et al, 2022), this suggests that DN thymocytes are much more heterogenous than previously thought.…”
Section: A Comprehensive Transcriptional Map Of Early T Cell Developm...supporting
confidence: 89%
See 4 more Smart Citations
“…High Trdc, Id3, Sox13 and Rorc identified mature γδ thymocytes (Fig 2D). This analysis revealed that multiple distinct populations correspond to each of the canonical DN stages and consistent with recent T cell development studies (Spidale et al, 2018;Sagar et al, 2020;Scaramuzzino et al, 2022), this suggests that DN thymocytes are much more heterogenous than previously thought.…”
Section: A Comprehensive Transcriptional Map Of Early T Cell Developm...supporting
confidence: 89%
“…The instructive model proposes that TCRγδ signals competes with pre-TCR(β) signals and the lineage decision is determined by cell specific interactions that activate key transcription factors, which in turn instructs gene expression program (Carpenter & Bosselut, 2010). In contrast, the stochastic selective model postulates that lineage commitment is determined prior to the onset of TCR gene rearrangement, and those thymocytes that receives appropriate TCR signaling that matches their hardwired identity further progress along the αβ versus γδ lineage and differentiate into a specific subset of γδ T cells (Scaramuzzino et al, 2022). Indeed, Scaramuzzino and colleagues showed that TCR signaling clearly has a role in γδ lineage maturation because LAT-deficient DN3 cells that express a γδ TCR are unable to complete the activation of the γδ T cell lineage, including expression of Sox13, Maf , and Cpa3 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations